Analisis Risiko Kecelakaan pada Pembuatan Produksi Tempe dengan Menggunakan Penerapan Metode HAZOP di CV Suryadi Sentosa - Ahmad Farozi Eka Chandra; Assifa Rizqiyah Fitriani; Adi Sukma Maulana; Budiharjo Budiharjo (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The Hazard and Operability (HAZOP) methodology is a qualitative risk analysis technique commonly used to detect potential work hazards. CV. Suryadi Sentosa, also known as Bapak Suryadi's Home Tempe Industry, is a home-based business that produces tempeh. Almost all of the production procedures are still carried out manually, and occupational accident analysis measures have not been implemented. The factory conditions indicate inadequate lighting and ventilation, as well as relatively slippery floors. It is also observed that the industry workers do not pay much attention to their posture, and they do not use personal protective equipment (PPE). This research was conducted directly at the CV. Suryadi Sentosa Tempe Factory, using interviews and observations of seven workers involved in the production process. The steps taken in this study are compiling the sequence of the production process. By using a Hazard and Operability (HAZOP) worksheet, identify potential risks, conduct risk control analysis, monitor and evaluate, implement improvements, and draw conclusions. The analysis found 9 stages of tempeh production at Mr. Suryadi's facility. Several improvements are needed, including involving several workers to handle soybean processing, creating ventilation to provide good and healthy air circulation for workers, adding lighting as a light source so that workers can perform their tasks comfortably, and using ergonomic chairs and work tables to prevent fatigue and increase factory productivity.